Pengaruh Hedonic Shopping Motivation, Visual Merchandising, dan Store Atmosphere Terhadap Impulse Buying Melalui Positive Emotion Sebagai Variabel Intervening Pada Konsumen Industri Retail Tiongkok di Indonesia - Lutfiani, Izah; Farisi, Herdian; Yuliana, Ade (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This research aims to analyze the impact of visual merchandising, store atmosphere, and hedonic shopping motivation on impulse buying, with positive emotion as a mediator for KKV Indonesia consumers. The research involved 120 respondents selected through purposive sampling. Data was collected through questionnaires and analyzed using the SEM-PLS method with the help of SmartPLS software. Based on the results, visual merchandising, store atmosphere, and hedonic shopping motivation significantly impact positive emotion. Positive emotion, in turn, has a significant effect on impulse buying. Positive emotion can act as a mediator in the relationship between visual merchandising, store atmosphere, hedonic shopping motivation, and impulse buying.